Secession conventions collection
Three copies of the South Carolina secession ordinance (1860 December 20), two copies of the Virginia ordinance (1861 April 17), and copies of the Florida (1861 January 10) and Louisiana (1861 January 26) ordinances. Persons represented include D. F. Jameson, John Janney, John C. McGehee, and Alexander Mouton.
Positive and negative photocopies and facsimiles.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jameson, D. F. -- 1810-1864.; Janney, John, -- 1798-1872.; McGehee, John C; Mouton, Alexander, -- 1804-1885.; Florida. -- Constitutional Convention -- (1861); Louisiana. -- Constitutional Convention -- (1861); South Carolina. -- Convention -- (1860-1862); Secession -- Southern States; Florida -- History -- Civil War, 1861-1865.; Louisiana -- History -- Civil War, 1861-1865.; South Carolina -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.